Organization of training loads of a various orientation by training of sportsmen-rescuers - Grigorenko, Дмитрий Николаевич; Grishchenkov, Александр Иванович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
On the basis of the analysis of reserve opportunities of energy provision of an organism and adequacy of response of the nervous-muscular apparatus on offered kinds of physical loads of sportsmen-rescuers are determined. Criteria of management of the training of sportsmen-rescuers on the basis of typology of adaptation to various modes of impellent activity are developed. The methods of modeling on the basis of criteria of forecasting of a final result in carrying out exercises are elaborated.